PENGARUH SOSIALISASI PAJAK, SANKSI DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KELURAHAN PASIR PUTIH - Lubis, Siti Abina; Sanulika, Aris (Publika Citra Media, 2024)
This research aims to determine the influence of tax socialization, sanctions and taxpayer awareness on taxpayer compliance in paying land and building taxes. This research uses a quantitative method with an associative approach, the population in this research is 15,939 PBB Taxpayers in Pasir Putih Subdistrict in 2022, with a sample size of 100 respondents calculated using the Slovin formula with an error rate of 10%, the sampling technique uses a technique simple random sampling. Data analysis methods use validity tests, reliability tests, classical assumptions, multiple regression analysis, coefficient of determination tests, T statistical tests, and F statistical tests with the help of SPSS version 26 software. The results of this research show that Tax Socialization, Sanctions and Taxpayer Awareness simultaneously influence Taxpayer Compliance. Partially, the Sanctions and Taxpayer Awareness variables have an effect on Taxpayer Compliance, while the Tax Socialization variable has no effect on Taxpayer Compliance. So it can be concluded that the lack of socialization that taxpayers see or find out about does not affect taxpayers' awareness of the importance of paying their obligations so that taxpayers can avoid applicable sanctions.